KAJIAN RESPON MASYARAKAT TERHADAP PEMBANGUNAN SMELTER DI KABUPATEN SUMBAWA BARAT - Umar Umar; Subhan Purwadinata; Suparman Suparman; Supriadin Supriadin (KARYA: Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of this Community Service Activity is to examine the response of the community and government regarding the smelter program. These activities were held in the villages of Benete and Maluk, West Sumbawa Regency. The activity which was held in December 2021 involved 126 participants. The details of the participants involved are 6 local government officials, 15 youth delegates, 15 community leaders, 15 religious leaders, and 15 community members who have a direct impact on the Smelter project in Maluk village, and 15 youth delegates, 15 people community leaders, 15 religious leaders, and 15 community leaders who have a direct impact on the Smelter project in Benete village. The method of carrying out activities is the structured interview method. PkM is carried out in three stages, namely; 1) planning, 2) implementation of activities, and 3) reporting of activities. The results of the analysis show that; 1) The local government supports the construction of a smelter in Sumbawa Regency in order to increase the wheels of development and improve the community's economy, and 2) People in Maluk and Benete villages strongly agree with the construction of a smelter in West Sumbawa Regency.